Scaffolding behavioral health concepts from more simple to complex builds NP students' competence. (April 2017) - Lauerer, Joy; Edlund, Barbara J.; Williams, Amy; Donato, Annemarie; Smith, Gigi
Abstract: Background: Behavioral health disorders (psychiatric illness and substance abuse disorders) represent a significant burden across the nation's health care system. About one half of the problems that present in primary health care settings are behavioral in nature. There is urgent need to improve the integration of behavioral health care services into primary care. Methods: The purpose of this paper is to describe how an asynchronous online graduate nurse practitioner program utilized a constructivist paradigm to creatively combine online problem based learning cases and on campus learning intensives to scaffold student learning. Results: Student E -value scores were high and comments reflected improved knowledge, skill and comfort managing behavioral health problems in a primary care setting. Conclusion: This innovative model can serve as a template for other educational programs and improve student's ability to identify, manage and treat common behavioral health care problems that present in primary care settings. Highlights: Primary care APRN's are uniquely positioned to improve the care of patients with behavioral health issues. The integration of behavioral health into primary care curriculum is an important challenge for graduate nursing programs. Scaffolding behavioral health concepts from more simple to complex builds NP competence.